Economy and ecology: a global approach - Almeida, Luciana Togeiro de (Universidade Estadual Paulista / UNESP, 2009)
This paper discusses Elmar Altvater's most recent contribution in international political economy, its subject being the global economic and ecological consequences of the diffusion of the fordist production system. It is paid special attention to the bleak thesis concerning the developing countries, which follows bom their ascribed path of poverty and environmental degradation in Altvater's model. It is argued that the reliance on supranational regulation to solve these countries' actual problems may face senous political and economic constraints.